Feature of water: A practical concept in water reuse - Xiao-Wen Chen; Yu-Qing Xu; Wen-Long Wang; Nan Huang (Water Cycle)
The increasing stringency of standards has highlighted challenges in high-standard wastewater treatment and water reuse. Current water quality assessment primarily relies on bulk properties like chemical oxygen demand (COD) and biological oxygen demand (BOD), which fail to capture the intricate characteristics of wastewater contaminants. The novel concept of “feature of water'', a multidimensional assessment system encompassing four primary indicators: quantitative concentration, compositional characteristics, transformation potential, and toxicological effects, is applied in the study. Unlike conventional linear approaches, feature of water provides a holistic perspective on wastewater composition, examining pollutant variations across temporal and spatial dimensions. Applications of the feature of water concept include the identification of refractory pollutants, evaluation of treatment processes, and the design of tailored treatment technologies. Case studies demonstrate its effectiveness in improving water treatment efficiency, reducing operational costs, and mitigating ecological risks. By transitioning from traditional linear water quality evaluation to a systems-based approach, the feature of water provides a robust methodology to meet the demands of high-standard wastewater treatment and water reuse, ensuring environmental sustainability and public health protection.